Event-Participant and Incremental Planning over Event-Based Social Networks - Cheng, Yurong; Yuan, Ye; Chen, Lei; Giraud-Carrier, Christophe; Wang, Guoren; Li, Boyang (IEEE transactions on knowledge and data engineering, 2021)
In recent years, online Event Based Social Network (EBSN) platforms have become increasingly popular. One typical task of EBSN platforms is to help users make suitable and personalized plans for participating in different interesting social events. Existing techniques either ignore the minimum-participant requirement constraint for each event, which is crucially needed for some events to be held successfully, or assume that events would not change once announced. In this paper, we address the above inadequacies of existing EBSN techniques. We formally define the Global Event Planning with Constraints (GEPC) problem, and its incremental variant. Since these problems are NP-hard, and provide approximate solutions. Finally, we verify the effectiveness and efficiency of our proposed algorithms through extensive experiments over real and synthetic datasets.